Study of respiratory metabolism for multimetal tolerant bacteria under metallic stress - Alhammadi, Eeman; Halimoon, Normala; Zulkeflee, Zufarzaana; Wan Johari, Wan Lutfi (Department of Environmental Sciences, Arak University, 2023)
In aquatic environments, excessive amounts of inorganic nutrients, such as heavy metals, pose a metabolic risk and threaten to halt microbial activity. Metal-resistant bacteria, through various metabolic activities, can treat and detoxify harmful inorganic compounds. Thus, higher energy and electron transport system (ETS) demands may be necessary for metal bioremediation, but cell viability may be affected. Therefore, the metabolic respiration activity of cells in the presence of Cu, Zn, Ni, and Cr individually and in the quaternary is an important aspect of this study that relies on estimating the action of respiration enzymes responsible for metabolic activity and glucose reduction over periods of metallic stress and growth phases. Three species of bacteria, including B. megaterium, S. ginsenosidimutans, and K. rhizophila, were isolated from the electroplating effluent and used to determine the activity level of catalase, dehydrogenase enzymes, and glucose reduction. Their ability to sustain metabolic activity and understand their role in conferring tolerance and bioremediation capabilities to bacteria was evaluated. The findings revealed that metabolic activity was greater during the exponential phase than during the stationary phase. Catalase production was less affected by high metal levels; additionally, sugar reduction was improved but decreased with increased metal levels, and growth progressed, in comparison to dehydrogenase activity, which was more sensitive to high metal levels. Although respiratory metabolism activity decreased with increasing cell age and high metal concentrations, metabolism and viability persisted under metallic stress. This establishes the tolerability of bacteria and recommends them for potential bioremediation of metallic pollutants and environmental clean-up.